Magento 2 DIY - Khliupko, Viktor (Distributed to the Book trade worldwide by Springer Science+Business Media New York, 2017)
This book teaches you how Magento 2, the newest version of the eCommerce platform, works. Aimed at entrepreneurs, marketers, and other experts interested in eCommerce, this book is accessible for anyone who wants to learn how to use Magento with no previous experience. Magento continues to be a top choice for eCommerce solutions in small and large businesses. Magento 2 DIY shows you how to set up and configure Magento for your own project. You will learn how to use extensions, templates and enterprise features. Various techniques are taught in an easy-to-understand way with real-world examples. Get started with Magento 2 using this book. .